Hubungan Antara Pola Makan, Aktivitas Fisik, Kualitas Tidur, Pengetahuan dan Pemberian Tablet Fe dengan Kejadian Anemia pada Remaja Putri di SMPN Baitussalam Aceh Besar - Latifah Zahra; Basri Aramico; Dedi Andria (Yayasan Literasi Sains Indonesia, 2026)
Anemia among adolescent girls is a public health concern that can affect academic performance, physical fitness, and reproductive health. Several factors are associated with anemia, including dietary patterns, physical activity, sleep quality, level of knowledge, and adherence to iron (Fe) tablet consumption. This study aimed to examine the relationship between these factors and the incidence of anemia among adolescent girls at SMPN 1 Baitussalam, Aceh Besar, in 2025. This study employed a cross-sectional design with a sample of 38 respondents selected using purposive sampling based on inclusion criteria. Primary data were collected using the Food Frequency Questionnaire (FFQ), Adolescent Physical Activity Recall Questionnaire (APARQ), Pittsburgh Sleep Quality Index (PSQI), a knowledge questionnaire, and a questionnaire on Fe tablet consumption. Data were analyzed using Fisher’s exact test with a significance level of 0.05. The results showed significant associations between dietary patterns, sleep quality, knowledge, and Fe tablet consumption with the incidence of anemia. In contrast, physical activity was not significantly associated with anemia. In conclusion, dietary patterns, sleep quality, knowledge, and adherence to Fe tablet consumption play important roles in preventing anemia among adolescent girls. Therefore, improving nutrition education, enhancing sleep quality, and strengthening Fe supplementation programs are recommended to reduce anemia prevalence.